STRATEGY TO IMPROVE ECONOMY COMMUNITY IN THE COVID-19 PANDEMIC THROUGH ESTABLISHING BADAN USAHA MILIK DESA - Yayuk Sulistiyowati (University of Islam Malang, 2021)
Mulyoagung Village established Badan Usaha Milik Desa (BUMDES) based on Law Number 6 of 2014 concerning Villages which requires all villages to have BUM Desa and with village funds so that funds can be allocated effectively and efficiently and not only for spending on consumables. The strategy of Bumdes Mulyoagung is very appropriate in an effort to provide support for local villagers during the COVID-19 pandemic. The existence of Bumdes Mulyoagung Village is still relatively new in the journey of Bumdes Mulyoagung, so a mature strategy is needed to build Bumdes Mulyoagung so that it can survive and develop more advanced in the future. The reason for this research is strengthened by the desire to drive the economy that starts from the village as a basic component of community development in supporting national development.